Identification of an Allelic Variant of the CsOr Gene Controlling Fruit Endocarp Color in Cucumber (Cucumis sativus L.) Using Genotyping-By-Sequencing (GBS) and Whole-Genome Sequencing - Kishor, D. S.; Lee, Hea-Young; Alavilli, Hemasundar; You, Chae-Rin; Kim, Jeong-Gu; Lee, Se-Young; Kang, Byoung-Cheorl; Song, Kihwan (Frontiers in Plant Science, 2021)
The cucumber is a major vegetable crop around the world. Fruit flesh color is an important quality trait in cucumber and flesh color mainly depends on the relative content of β-carotene in the fruits. The β-carotene serves as a precursor of vitamin A, which has dietary benefits for human health. Cucumbers with orange flesh contain a higher amount of β-carotene than white fruit flesh. Therefore, development of orange-fleshed cucumber varieties is gaining attention for improved nutritional benefits. In this study, we performed genotyping-by-sequencing (GBS) based on genetic mapping and whole-genome sequencing to identify the orange endocarp color gene in the cucumber breeding line, CS-B. Genetic mapping, genetic sequencing, and genetic segregation analyses showed that a single recessive gene (CsaV3_6G040750) encodes a chaperone DnaJ protein (DnaJ) protein at the Cucumis sativus(CsOr) locus was responsible for the orange endocarp phenotype in the CS-B line. The Or gene harbored point mutations T13G and T17C in the first exon of the coding region, resulting in serine to alanine at position 13 and isoleucine to threonine at position 17, respectively. CS-B line displayed increased β-carotene content in the endocarp tissue, corresponding to elevated expression of CsOr gene at fruit developmental stages. Identifying novel missense mutations in the CsOr gene could provide new insights into the role of Or mechanism of action for orange fruit flesh in cucumber and serve as a valuable resource for developing β-carotene-rich cucumbers varieties with increased nutritional benefits.